SIKAP BANGLADESH DALAM MENANGGAPI PROGRAM UNHCR “UNITED NATIONS JOINT INITIATIVE” TERHADAP PENANGANAN PENGUNGSI ROHINGYA (PERIODE 2006-2011) - ", Mery; Olivia, Yessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research explains Bangladesh’s response about UNHCR’s “United Nations Joint Initiative” in handling Rohingya refugees in Bangladesh. Bangladesh is now home to 29.016 Rohingyas. The refugees has caused social and economic problems for Bangladeshi goverment over 33 years. UNJI was proposed by UNHCR to help Rohingyas ang Bangladeshis.The research applies qualitative methods, and case study in this research the data collected through library research, literature studies, official documents, academic journal, mass media.Bangladesh refused UNHCR proposal becouse UNJI has caused security threat to the country of Bangladesh. That UNJI provide assistance to Refugees without care about what will happend to local people, it seen from the more dense the population, the strunggle for jobs, and food shortages. That means UNJI did’n’t fully resolved the facing problem in Bangladesh.Keywords : Bangladesh, Refugees, UNJI, Socio-Economy, Security.